2019
DOI: 10.1371/journal.pgen.1008467
|View full text |Cite
|
Sign up to set email alerts
|

Gpr63 is a modifier of microcephaly in Ttc21b mouse mutants

Abstract: The primary cilium is a signaling center critical for proper embryonic development. Previous studies have demonstrated that mice lacking Ttc21b have impaired retrograde trafficking within the cilium and multiple organogenesis phenotypes, including microcephaly. Interestingly, the severity of the microcephaly in Ttc21baln/aln homozygous null mutants is considerably affected by the genetic background and mutants on an FVB/NJ (FVB) background develop a forebrain significantly smaller than mutants on a C57BL/6J (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…With a few exceptions (e.g. Gpr88, Gpr161, Gpr63 and EP4 contain LPG motifs in their CTs 27,36 ), the same exact motifs are not present in these other receptors. Still, many of them have similar motifs that could potentially perform the same function (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…With a few exceptions (e.g. Gpr88, Gpr161, Gpr63 and EP4 contain LPG motifs in their CTs 27,36 ), the same exact motifs are not present in these other receptors. Still, many of them have similar motifs that could potentially perform the same function (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond HTR6 orthologs, most known ciliary GPCRs do not have these exact same motifs (not shown). Still, there are exceptions (e.g., GPR88, GPR161, GPR63, and PTGER4 all have LPG motifs in their CTs ( 34 , 42 )), and most ciliary GPCRs do have similar motifs that may potentially perform the same function (e.g., many have RK or similar motifs in their IC3s). However, for these analyses to be more meaningful, we would need to know which residue substitutions preserve or disrupt CTS function at each position within the motif.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using murine models on inbred background have provided valuable information as to the factors that contribute to phenotypic variability ( Nadeau, 2001 ; Hamilton and Yu, 2012 ; Kousi and Katsanis, 2015 ). Numerous studies have reported different levels of phenotypic severity on various inbred backgrounds ( Jones et al, 2008 ), as utilization of these strains can more readily identify genetic modifiers via SNP array, GigaMuga and quantitative trait locus (QTL) analysis ( Morgan et al, 2015 ; Snedeker et al, 2019 ). Studies such as these have been instrumental in identifying genetic modifiers that can contribute to increasing the variability of phenotypic presentations in ciliopathies.…”
Section: Discussionmentioning
confidence: 99%